National idea in the lyrics of Nurlan Maukenuly - Kelgembayeva Б.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the philosophical and social significance of the concept of national idea and its artistic embodiment in Kazakh poetry of the 1980s-1990s, particularly in the lyrics of Nurlan Maukenuly. According to the author, the art of words represents a unique form of social consciousness that aesthetically explores the national idea and awakens national self-awareness. In this context, the aim of the article is to analyze the manifestations of the national idea in the poetic works of N. Maukenuly and his contemporaries, such as T. Medetbek, T. Abdikakimov, and E. Raushanov. The researcher emphasizes the artistic mastery of these poets in conveying the national idea and awakening national consciousness. Special attention is given to N. Maukenuly’s poetic power, his philosophical reflections on pressing issues of the past and present, as well as his ability to reveal the contradictions of Kazakhstani society. The author provides concrete examples proving that Nurlan’s poetry revives the spirit of nationhood and heroism characteristic of the works of Asan Kaigy, Kaztugan, Shalkiyz, Dospambet, Bukhar, Aktamberdi, and Makhambet. Moreover, the article explores the aesthetic interpretation of the consequences of colonialism, the totalitarian system, and their impact on national consciousness and identity. The study concludes that N. Maukenuly is a true national poet capable of reviving the national idea deeply rooted in the nation’s self-awareness.